DOI: 10.11606/d.11.1998.tde-20220208-105006
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento e teste de modelos agrometeorológicos para a estimativa de produtividade do cafeeiro (>i<Coffea arabica>/i< L.) a partir do monitoramento da disponibilidade hídrica do solo

Abstract: Desenvolvimento e teste de modelos agrometeorológicos para estimativa de produtividade do cafeeiro ( Coffea arabica L.) a partir do monitoramento da disponibilidade hídrica do solo/ Angélica Giarolla Picini. --Piracicaba, 1998. 132 p. Dissertação (mestrado) -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Studies with orbital imaging have already observed a relationship between the index and productivity. They are generally used in spectral agrometerological models, with NDVI being the spectral component representing the leafing aspects of the crop (Picini, 1998;Rosa et al, 2010;Silva et al, 2011;Bernardes et al, 2012;Almeida et al, 2017). The NDVI multiple regression equation obtained by UAS images, can be used in large-scale mapping, enabling to estimate productivity at the plant level and thus exercise greater accuracy in precision agriculture.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with orbital imaging have already observed a relationship between the index and productivity. They are generally used in spectral agrometerological models, with NDVI being the spectral component representing the leafing aspects of the crop (Picini, 1998;Rosa et al, 2010;Silva et al, 2011;Bernardes et al, 2012;Almeida et al, 2017). The NDVI multiple regression equation obtained by UAS images, can be used in large-scale mapping, enabling to estimate productivity at the plant level and thus exercise greater accuracy in precision agriculture.…”
Section: Resultsmentioning
confidence: 99%